2009
DOI: 10.1128/aem.01377-08
|View full text |Cite
|
Sign up to set email alerts
|

A Chromosomally LocatedtraHIJKCLMNOperon Encoding a Putative Type IV Secretion System Is Involved in the Virulence ofYersinia ruckeri

Abstract: Nucleotide sequence analysis of the region surrounding the pIVET8 insertion site in Yersinia ruckeri 150RiviXII, previously selected by in vivo expression technology (IVET), revealed the presence of eight genes (traHIJKCLMN [hereafter referred to collectively as the tra operon or tra cluster]), which are similar both in sequence and organization to the tra operon cluster found in the virulence-related plasmid pADAP from Serratia entomophila. Interestingly, the tra cluster of Y. ruckeri is chromosomally encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…Such effects have been recognized since the 1960s, but in most reported cases, polar effect mutations are detrimental, interfering in some way with proper transcription or translation of a downstream gene (46)(47)(48)(49)(50). The predominantly adverse effects of reported polar mutations may be due to previous selection for bases or codons that function well under typical growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have been recognized since the 1960s, but in most reported cases, polar effect mutations are detrimental, interfering in some way with proper transcription or translation of a downstream gene (46)(47)(48)(49)(50). The predominantly adverse effects of reported polar mutations may be due to previous selection for bases or codons that function well under typical growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The application to Y. ruckeri of in vivo expression technology (IVET) has allowed the identification of 14 genes specifically induced during the infection process in rainbow trout (11). Some of them have been proven to participate in virulence, such as the iron uptake mechanism via the catecholate siderophore ruckerbactin (11), the YhlA hemolysin (13), and the tra chromosomally located operon, a type IV secretion system (22).…”
mentioning
confidence: 99%
“…Proteins using this pathway can be secreted into the extracellular milieu or directly into a host cell. In Y. ruckeri, the traHIJKCLMN operon, which encodes a putative type IVb secretion system, is involved in the virulence of the bacterium (Méndez et al, 2009). LD 50 determinations with rainbow trout fry indicated that a mutation in the traI gene resulted in virulence attenuation.…”
Section: Protein Secretion Systemsmentioning
confidence: 99%
“…LD 50 determinations with rainbow trout fry indicated that a mutation in the traI gene resulted in virulence attenuation. It is suggested that this system contributes to bacterial pathogenicity through the secretion of some effector molecules into the host cells (Méndez et al, 2009). …”
Section: Protein Secretion Systemsmentioning
confidence: 99%